STUDY OF GAMMA ABSORPTION PROPERTIES OF WATER SOLUBLE SULPHATE COMPOUNDS AT DIFFERENT ENERGY LEVELS - S.R., MITKARI; V.P., DESHMUKH; S.M., DONGARGE (Innovare Journal of Sciences, 2020)
Objective: Linear and Mass attenuation coefficients are two quantities used, their strategies of measurement had been evolved by many peoples for stable and aqueous solutions. we have tried to broaden an equation for direct dimension of linear attenuation coefficient of water soluble sulphates at one of a kind energys. This approach is useful in measuring the absorption coefficient of sulphate without obtaining them in pallet form. Materials and Methods: Water soluble sulphates were collected from study sites. Here we have given Ammonium sulphate((NH₄)₂SO₄), Sodium sulphate (Na₂SO₄), Copper (II) sulphate( CuSO₄ₓ), Zinc sulphate( ZnSo4) and water. Results: linear and mass attenuation coefficient of water soluble Sulphate for distinct concentrations and anticipated from them the attenuation coefficient for compound through the use of the aggregate rule developed via Teli (1998) hooked up the validity and utility of the solution technique. This approach is simple and avoids the need of training of pure crystalline compound for experiment there via saving time and expenditure. The version of awareness of answer is made easy by using adding water to solution without changing the compound quantity in it. Conclusion: This saves the compound amount and thus in addition economizes the experiment.